2003
DOI: 10.2754/avb200372040499
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Voluntary Consumption of Amino Acid-chelated Iron in Preventing Aaemia of Suckling Piglets

Abstract: The aim of the study was to evaluate efficiency of voluntary access to amino acid-chelated iron in the form of mineral supplement in preventing anaemia of piglets. Piglets in group 1 (n = 60) were offered ad libitum the iron mineral supplement (Fe 110 g·kg -1 ) from the 2 nd to the 14 th day of life. Piglets in group 2 (n = 30) were given 200 mg Fe 3+ as iron dextran i.m. on day 3. On day 7, haemoglobin concentration (Hb) (P < 0.05), packed cell volume (P < 0.05), red blood cell count (P < 0.01) and plasma iro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
(2 reference statements)
0
2
1
Order By: Relevance
“…This demonstrates that the chelated iron did not influence the performance of piglets, but the supply of injectable iron dextran was essential for piglet development. These results contradict the findings of Svoboda and Drabek (2003), which conclude that free access to a commercial product containing iron chelated with aminoacid vehicles prevents piglet anemia and results in piglet growth comparable to that of piglets that received injectable iron dextran.…”
Section: Discussioncontrasting
confidence: 83%
“…This demonstrates that the chelated iron did not influence the performance of piglets, but the supply of injectable iron dextran was essential for piglet development. These results contradict the findings of Svoboda and Drabek (2003), which conclude that free access to a commercial product containing iron chelated with aminoacid vehicles prevents piglet anemia and results in piglet growth comparable to that of piglets that received injectable iron dextran.…”
Section: Discussioncontrasting
confidence: 83%
“…Svoboda and Drábek (2003) found that voluntary consumption of amino acid chelated iron resulted in the prevention of anaemia in the majority of weaned piglets. The piglets were offered a mineral supplement with amino acid chelated iron (110 g Fe/kg) ad libitum from day 2 to day 14 of life.…”
Section: Chelatesmentioning
confidence: 98%
“…Current iron supplementation husbandry practises have several potentially adverse repercussions such as iron toxicity, inducing oxidative stress [5], secondary infections predisposing piglets to arthritis [10], elevated production costs associated with individual supplementation protocols [30] and compromised welfare linked with needlestick injuries and poor hygiene [11]. Previous attempts at voluntary oral iron supplementation have demonstrated disappointing piglet responses, resulting in insufficient iron intake to combat IDA [8,18]. In attempting to overcome this by the addition of flavour masking agents, this study demonstrated that flavour-conditioned piglets had increased interactions with anise-flavoured creep feed but did not increase their creep consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, increased handling times and the unpleasant metallic taste of high-dosage iron supplements may negatively impact piglet behaviour [16]. Furthermore, non-injected piglets subject to voluntary intake of oral iron supplements were all reported to exhibit anaemia within the first two weeks of life due to inadequate iron consumption [8,17,18]. In contrast, Maes et al [11] demonstrated that an iron-rich diet (24% iron content) provided to non-injected piglets three times in specialised feeders reduced the variability of voluntary iron intake to successfully combat anaemia and even surpassed blood Hb concentrations when compared to iron-injected piglets.…”
Section: Introductionmentioning
confidence: 99%